A review of varietal change in roots, tubers and bananas: consumer preferences and other drivers of adoption and implications for breeding. (26th July 2020) - Thiele, Graham; Dufour, Dominique; Vernier, Philippe; Mwanga, Robert O. M.; Parker, Monica L.; Schulte Geldermann, Elmar; Teeken, Béla; Wossen, Tesfamicheal; Gotor, Elisabetta; Kikulwe, Enoch; Tufan, Hale; Sinelle, Sophie; et al.
Summary: This review of the literature on varietal change in sub‐Saharan Africa looks in detail at adoption of new varieties of bananas in Uganda, cassava in Nigeria, potato in Kenya, sweetpotato in Uganda and yams in Côte d'Ivoire. The review explored three hypotheses about drivers of varietal change. There was a strong confirmation for the hypothesis that insufficient priority given to consumer‐preferred traits by breeding programmes contributes to the limited uptake of modern varieties (MVs) and low varietal turnover. Lack of evidence meant the second hypothesis of insufficient attention to understanding and responding to gender differences in consumer preferences for quality and post‐harvest traits was unresolved. The evidence on the third hypothesis about the informal seed system contributing to slow uptake of MVs was mixed. In some cases, the informal system has contributed to rapid uptake of MVs, but often it appears to be a barrier with inconsistent varietal naming a major challenge. Abstract : Two metrics widely used to measure the overall impact of breeding programs are: (i) adoption of modern varieties as a percentage of the total area under the crop, and (ii) the area‐weighted varietal age of a crop in a particular country or region, estimated as the average time since the release of varieties, weighted by the area across which they are adopted. The graph compares this data for roots tubers and bananas with other crops based on information gathered in 2010 (Walker & Alwang, 2015). The paper provides an update through case studies of varietal change in banana, cassava, potato, sweetpotato and yam.